Figure 2 from: Sheffield CS, Oram R, Heron JM (2020) Bombus (Pyrobombus) johanseni Sladen, 1919, a valid North American bumble bee species, with a new synonymy and comparisons to other "red-banded" bumble bee species in North America (Hymenoptera, Apidae, Bombini). ZooKeys 984: 59-81. https://doi.org/10.3897/zookeys.984.55816 - Sheffield, Cory S.; Oram, Ryan; Heron, Jennifer M. (Zenodo, 2020)
Figure 2 Holotype female of Bombus sylvicola var. johanseniA face B lateral view C associated specimen labels D dorsal view. Photographs by Joel Kits, Ottawa Research and Development Centre.